Clinical and Radiographic Comparison between Piezoelectric Implant Osteotomy Preparation versus Conventional Drilling Technique - Elmokadem , Mohamed Samy; Hamed , Mohamed Said; Desouky , Gihan Gamal El (Journal of Neonatal Surgery, 2025)
Abstract Piezo-surgery was introduced for implant site preparation due to its atraumatic capabilities in preparation of the recipient bed thus offering improved osseointegration and better bone healing. Objective: to evaluate the effect of using Piezoelectric bone surgery for implant osteotomy preparation on implant stability and osteointegration compared with conventional drilling techniques. Methods: 16 implants equally installed in the maxillary anterior or premolar regions of adult patients, divided into two groups: Group I where the implant osteotomy site was performed using conventional drills. Group II where the implant osteotomy site was performed using specific piezoelectric inserts. All implants were clinically evaluated for implant stability using OSTELL device immediately after implant placement and 6 months postoperatively, as well as radiographically by digital parallel periapical tecgnique immediately post-opertively, then after three and six months to assess changes in relative bone density using digora software. Results: Both groups showed a significant increase in implant stability values (ostell readings) throughout the study period. Piezoelectric osteotomy group showed statistically higher Ostell values after six months in comparison to the conventional drilling group. Radiographic evaluation showed that relative bone density values increased for both groups at the apex, mesial and distal implant aspects throughout the study period, with the highest density values at the six months period. Comparison in density values between both groups showed statistically higher bone density values in the piezoelectric osateotomy group after six months. Correlation between clinical implant stability values (Ostell readings) and radiographic bone density values showed a significant positive correlation at the six months follow-up period. Conclusions: Osseointegration is improved surrounding implants inserted in bone when Piezoelectric drilling is used for drilling of osteotomy sites in the anterior maxillary region can be a successful option for increasing implant stability values throughout the healing period in comparison to conventional drilling techniques.